Altered Expression of Three EGFR Posttranslational Regulators MDGI, MIG6, and EIG121 in Invasive Breast Carcinomas - Didier Meseure; Kinan Drak Alsibai; Sophie Vacher; Rana Hatem; Andre Nicolas; Celine Callens; Florence Lerebours; Ivan Bieche (Analytical Cellular Pathology)
Epidermal growth factor receptor (EGFR) signalling is a highly regulated process with a tight balance between receptor activation and inactivation in invasive breast carcinomas (IBCs) particularly in triple-negative carcinomas (TNC). Clinical trials using anti-EGFR therapies are actually performed although no activating alterations (mutations, amplifications, or rearrangements) of EGFR have been clearly recognized in order to identify new targeted modalities for IBCs. We explored mammary-derived growth inhibitor (MDGI), estrogen-induced gene-121 (EIG121), and mitogen-induced gene-6 (MIG6), three posttranslational EGFR trafficking molecules implicated in EGFR spatiotemporal regulatory pathway. We quantified MDGI, EIG121, and MIG6 at mRNA levels by using real-time quantitative RT-PCR in a series of 440 IBCs and at protein levels by using immunohistochemistry in a series of 88 IBCs. Results obtained by RT-PCR showed that in IBCs, MDGI, MIG6, and EIG121 mRNA were mainly underexpressed (25.7%, 45.0%, and 16.1%, respectively) particularly in the TNC subtype for EIG121 (60.3%). We also observed mRNA overexpression of MDGI and EIG121, respectively, in 12.7% and 22.3% of IBCs. These altered mRNA expressions were confirmed at the protein level. Some links were found between expression patterns of these three genes and several classical pathological and clinical parameters. Only EIG121 was found to have a prognostic significance (p=0.0038). Altered expression of these three major EGFR posttranslational negative regulators could create an aberrant EGFR-mediated oncogenic signalling pathway in IBCs. MDGI, MIG6, and EIG121 expression status also may be potential useful biomarkers (sensitivity or resistance) in targeted EGFR therapy.